Disponibilité des produits forestiers non ligneux fondamentaux à la périphérie du Parc national de Lobeke - Péguy Tonga Ketchatang; Louis Zapfack; Louis-Paul-Roger Kabelong Banoho; Dominique Endamana (VertigO)
Non-Timber Forest Products are appropriate to meet the needs of local and indigenous communities surrounding the National Park of Lobéké. In order to better assess their availability, a botanical inventory has been carried out. The methodology use to develop the inventory consist into the establishment of transect2 in the village of Mambélé. The village is located in the area of the Tri National of Sangha, more precisely in the South-East of Cameroon. In total, 9 transects of 2 km long and 20 m large allow the team to cover an area of 36 ha. Therefore, these transects helped identifying 29 individuals of Irvingia gabonensis, 204 individuals of Ricinodendron heudelotii, 54 individuals of Entandrophragma cylindricum, and 154 individuals of Terminalia superba. In addition, some interesting results are coming out from the calculation of species densities and variances analysis with ANOVA methodology : the availability of each species was linked mainly to two parameters, which include the type of land use area (old secondary forest, secondary forest, swamp forest, young fallow and old fallow) and the distance for harvesting. Therefore, most of identify species are found in secondary forests and old secondary forests. From the analysis, we notice that the diameter class] 20-40 [ is the class where we found most individuals from each species. To conclude, domestication of these Non-Timber Forest Product could be recommended as an alternative option to strengthening the economy and thus contributing to the conservation of biodiversity.